Damping Optimization in Simplified and Realistic Disc Brakes - Wehner, Jan-Hendrik (SpringerBriefs in Applied Sciences and Technology,, 2018)
The main goal of this book is to show how to modify and optimize the properties of the damping matrix in order to find the most beneficial way of adding damping to a given mechanical system. To this end, a two-degree-of-freedom model of disc brake is analyzed to gain insight into the fundamental physical behavior of damping. In addition, more realistic, high-dimensional finite element brake models are studied and optimized for stability.